Developing peer-assessment based station rotation learning model to enhance students’ cucurbit flute skills and learning motivation: A need assessment research - Yi, Qin; Petsangsri, Sirirat; Ratanaolarn, Thanin; Cui, Jianming (Edelweiss Applied Science and Technology, 2025)
This study aims to address pedagogical challenges in cucurbit flute (hulusi) education—such as limited instructional resources, teacher-centered approaches, and low student engagement-by proposing a peer-assessment-based station rotation model to enhance students’ performance skills and learning motivation. Grounded in constructivism and self-determination theory, the research employed a mixed-methods design, combining structured interviews with five teachers and a 5-point Likert scale questionnaire administered to 150 students to assess needs. Findings revealed strong consensus among both teachers and students on the necessity of improving current teaching methods, with particular emphasis on fostering motivation and technical proficiency. The proposed model, validated through literature review and expert evaluation, integrates peer feedback within a rotational learning framework to promote active engagement and collaborative skill development. Results suggest that this approach can bridge gaps in traditional instruction by creating a more interactive and student-centered learning environment. The study contributes to music education by offering an innovative pedagogical model tailored to cucurbit flute instruction, with practical implications for educators seeking to enhance student motivation, peer collaboration, and cultural preservation in traditional music training. Future research could explore its applicability to other niche instruments and diverse educational settings.